GENERIC framework for the Fokker-Planck equation - Hoyuelos, Miguel Luis (2015)
The GENERIC theory provides a framework for the description of non-equilibrium phenomena in isolated systems beyond local thermal equilibrium and beyond linear non-equilibrium (i.e., linear relations between thermodynamic forces and currents). The framework is applied to a system described by a Fokker-Planck (FP) equation combined with its reservoir. It is shown that chemical reactions (with stationary solution satisfying detailed balance) can be included in the framework.